The Quality of Four-Tier Diagnostic Test Misconception Instrument for Parabolic Motion - Maison Maison; Dwi Agus Kurniawan; Retno Sari Widowati (Universitas Pendidikan Ganesha, 2021)
This study aims to find out how the process of developing instrument products in the form of a four-tier diagnostic test on parabolic motion material, and to find out how the quality of a four-tier diagnostic test instrument product on parabolic motion material was developed. The test subjects were all high school students of class X MIPA, taken by purposive sampling, namely 60 students in the first phase of the trial and 134 students for the 2nd phase of the trial. of 0,3 which means valid. The instrument reliability value is 0,859 which is in the very high reliability category. This means that the developed instrument can be used to identify misconceptions. The results of expert validation indicate that the instrument is in the very good category so that it can be used to identify misconceptions. The validation results from the first validator are 85% (Good) and the second validator is 92,08% (very good). Based on the results of the study, it can be concluded that the misconception instrument developed from one-tier questions to four-tier diagnostic tests is appropriate to be used to identify students' misconceptions on parabolic motion material. This can be seen from the results of the analysis of the validity and reliability of the instrument, where all items are valid and have very high reliability.